Madrasah dan Pembelajaran Berdiferensiasi: Peran dan Strategi Pemberdayaan Guru Madrasah dalam Implementasi Pembelajaran Berdiferensiasi pada Madrasah Ibtidaiyah Swasta - Murdjoko, Murdjoko; Aslamiah, Aslamiah; Cinantya, Celia; Kamsiah, Kamsiah (FKIP Universitas Wisnuwardhana, 2025)
This study aims to analyze the roles and strategies of teacher empowerment in implementing differentiated instruction at Private Madrasah Ibtidaiyah and its impact on learning effectiveness. Using a qualitative case study approach at three madrasahs in Gambut Subdistrict, the research highlights teachers' strategic roles as designers, facilitators, and evaluators of adaptive learning. Differentiation implementation involves adjusting content, process, product, and learning environments to meet students' needs. Empowerment strategies include intensive training, local-based approaches, and community collaboration. The findings indicate significant improvements in student motivation, participation, and creativity due to teacher empowerment. Recommendations emphasize the need for continuous training, optimized supporting facilities, and cross-sector collaboration to sustainably enhance differentiated learning quality.